ANALISA FAKTOR PENGELOLAAN RUMAH SAKIT YANG MEMPENGARUHI KEPUASAN KERJA DOKTER DI RUMAH SAKIT HERMINA - Dayeng, Adek Novita; Sinaga, Jon Piter; Ginting, Selamat (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2019)
The forms of services in hospital is include being able to serve patients suffering from illness, friendliness and the alertness of doctors, nurses and employees so that satisfaction and loyalty of hospital service users will be formed and patients will put their trust and commitment to in the hospital and patients will eventually use the services in the hospital in the future. An important problem related that to doctor job satisfaction that need to be considered by the hospital as the quality of hospital management. The purpose of this research is to find out that effect the job satisfaction of doctors at Hermina Hospital. The type of research is observational analytic with a cross sectional approach with a total number of 76 respondents with a Non Probability Sampling tehnique with a total sampling method. Data analysis was performed by Chi Square data testing and multiple logistic regression. The result of this research that the work satisfaction variable of doctors at Hermina Hospital which has a significant relationship is the variable working environtmen conditions pesonal dependent and interpersonal dependent variables. The most dominant variable is the interpesonal relationship variable. It is recommended to the hospital to be able to improve the quality of facilities, facilities and infrastucture which according to the assessment of doctors who have not yet adjusted to their expectations. It is expected that hospital will conduct training, or continue the education to improve the quality of services and Human Research Development performance. Hospital should be clean, neat and posess comfortable physical evidence when doctors are providing services to patients.